The effectiveness of preoperative chlorhexidine gluconate in prevention of surgical site infections in neonates - Tayseer Mostafa Gad; Khaled Mohamed El-Asmar; Nehal Mohamed El-Raggal; Filsan Abdi Mahmoud; Ayah Mohamed Shabana (Egyptian Pediatric Association Gazette)
Abstract Background and objective Newborns are particularly vulnerable to infection-related complications, including surgical site infections (SSIs). Chlorhexidine gluconate (CHG) demonstrates efficacy in reducing infant sepsis in resource-constrained settings. This study evaluated the effectiveness of preoperative bathing with 2% CHG compared to non-irritant plain soap in reducing postoperative wound infections following clean/clean-contaminated surgeries. Patients and methods This randomized trial involved 50 full-term newborns undergoing clean/clean-contaminated surgeries. Subjects were divided into two groups: CHG (2% chlorhexidine gluconate baths) and control (soap baths) groups, both administrated preoperatively. The primary outcome was the incidence of SSIs, while secondary outcomes included overall clinical parameters and the safety profile. Results The Chlorhexidine group showed lower rates of SSIs, mortality, and hospital stays (P < 0.01, 0.034, 0.041 respectively). Furthermore, patients in the CHG group required less postoperative mechanical ventilation and central line insertion (P < 0.05 for both). The application of CHG was also associated with a higher incidence of negative blood and wound cultures, with only transient, localized erythema occurring in only four treated neonates. Conclusion Preoperative bathing with 2% CHG significantly reduced postoperative SSIs in full-term neonates recovering from clean or clean-contaminated operations while demonstrating an excellent safety profile in this population.